Dermal formulation based on carbopol and Gum Arabic improves skin retention of indomethacin - Hiroko Otake; Ogata Fumihiko; Yosuke Nakazawa; Manju Misra; Masanobu Tsubaki; Naohito Kawasaki; Noriaki Nagai (PLoS ONE, 2025)
Top-down approaches efficiently convert hydrophobic drugs into nanoparticles, and the selection of appropriate additives is critical for successful nanoparticle formulation. Methylcellulose is an additive capable of reducing the drug particle size to less than 200 nm using the wet bead milling method, a breakdown method, and a dermal gel containing indomethacin (IMC) nanocrystal formulated with methylcellulose, which achieved high skin absorption. In this study, we focused on gum arabic (GA) as an alternative additive to methylcellulose and demonstrated whether formulations (carbopol gels) containing IMC nanocrystals with GA for dermal application (IMC-NP@GCgel) enhanced the local and systemic absorption of IMC. The particle size was significantly reduced by bead milling with GA, and the mean particle size of the IMC-NP@GCgel was 40–200 nm. The drug release and skin permeability from IMC-NP@GCgel was higher than those from carbopol gels containing the IMC microcrystals (mean particle size was 15.6 µm, IMC-MP@GCgel). In addition, IMC levels in the skin tissue of rats treated with the IMC-NP@GCgel were higher than those of rats treated with the IMC-MP@GCgel. However, the plasma IMC levels did not differ between the IMC-MP@GCgel- and IMC-NP@GCgel-treated rats. We successfully designed IMC nanocrystals using GA instead of methylcellulose. Moreover, we found that the addition of GA supported the absorption of IMC nanocrystals and enhanced the skin retention of the drug without increasing plasma IMC levels. These results provide useful information for the development of dermal formulations based on nanocrystals.